Computational modelling of polymer-based drug delivery systems - Mackenzie, R.C. (2015)
Polymer-based drug delivery systems have fantastic potential in chemotherapy as they can reduce drug side effects, help in patient compliance and provide targeting. Nanoprecipitation is used to encapsulate small drug molecules into polymer nanoparticles to form a drug delivery system. A major obstacle in polymer-based drug delivery systems reaching the clinic is their inability to load sufficient drug molecules. Little is known about the processes involved in the encapsulation of drug molecules into these delivery systems. An insight into the processes that govern the formation of these particles and encapsulation of small drug molecules within them is therefore desirable. We used molecular dynamics to model nanoprecipitation by simulating the dispersion of an acetone drop, containing polymer, into water containing drug. To allow sufficient dispersion of acetone a large amount of water is required, thus coarse-graining becomes mandatory. However, we maintain accuracy for our polymer-drug interactions by using a multiscale force field. Atomistic polymer and drug molecules contain coarse-grain virtual sites which facilitate interactions with the coarse-grain solvent molecules. We also employed fully atomistic reference simulations via resolution transformation to optimise our multiscale force field. This thesis details the theory and design behind this model of nanoprecipitation including how other techniques produced inferior results. Initial simulations with our multiscale model matched an experimental trend and were shown to be accurate relative to atomistic reference simulations. We also analysed a fully atomistic simulation of nanoprecipitation that took several months to complete. This atomistic simulation was used as a reference to update the multiscale force field. The updated force field improved on some aspects of the simulation but there are still areas that need improvement. Insight from the simulations provides an understanding of the experimental results and trends. The transferability of the model should help in designing more efficient polymer-based drug delivery systems in the future. We conclude with future work on modelling polymer-based drug delivery systems including alternate methods to gain understanding of not only drug incorporation but also drug release.